Hermeneutika Hukum: Studi Penafsiran Hukum menurut Paul Ricoeur dalam Konteks Putusan Mahkamah Konstitusi - Marselinus Sudandri Cancak; Mas Agus Priyambodo (Decisio: Jurnal Ilmiah Hukum, 2026)
Legal interpretation lies at the heart of legal practice, a process encompassing both subjectivity and objectivity. This research aims to analyze legal hermeneutics, specifically focusing on the thought of Paul Recoeur, and to apply it within the context of constitutional court decisions. Paul Ricoeur offers a rich framework for understanding text and action, which is highly relevant for unravelling the complexity of constitutional interpretation. Through literature analysis and case studies of specific constitutional court decisions, this research will explore how Paul Ricouer’s Concepts such as the “hermeneutical arc” (explanation-understanding-application), distanciation, the surplus of meaning, and the ethics of interpretation can provide new insights into the methods and outcomes of legal interpretation by constitutional judges. It is hope that this research can enrich the discourse on the theory of legal interpretation and provide a practical contribution to understanding the philosophical foundation behind the key decisions of the constitutional court